The Effect of Different Image Processing Techniques on the Measurement Accuracy of Endodontics File Length - Sima Nikneshan; Rabieh Boroumand; Nasim Esmaeeli; Ali Azadikhah; Maryam Paknahad (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Different software capabilities have been used in digital systems to increase the diagnostic quality of radiographic projections. Considering the availability of different enhancement techniques, it is necessary to determine the suitability of each technique for various diagnostic cases. There is controversy between studies over the effect of different digital enhancement techniques on the accuracy of file length measurements in endodontics. Purpose: The present in vitro study aimed to determine the effect of the software capabilities on the diagnostic accuracy to determine endodontic file lengths in photostimulable phosphor (PSP) radiographs. Materials and Method: In the present in vitro study, standard access cavities were prepared in 44 extracted human single-rooted permanent teeth. An endodontic file was placed in each root canal. PSP sensors were used for digital imaging using the parallel technique. All the images were reviewed on a same monitor; once normally with no software enhancement and once using software manipulations including pseudo-color, sharpness, emboss, and edge enhancement. The distance from the file tip to the rubber stop was measured on the images by an electronic ruler. Results: Significantly, all of the image enhancement techniques presented shorter measurements comparing to the actual length. The results revealed the significant accuracy of the measured error in the pseudo-color enhancement technique compared to other techniques. Conclusion: The results revealed significant differences between the initial measurements (the gold standard) and those made on the manipulated radiographs. In all cases, the measurements were significantly lower than the real values. Therefore, none of these digital enhancement techniques can increase the accuracy of file length measurements significantly. However, manipulation with the pseudo-color option resulted in fewer errors compared to other options and the normal images. Hence, for precise measurements of the endodontic file lengths, pseudo-color processing algorithm can be suggested when using PSP sensors.